The Prevalance and Radiographic Evaluation of Mandibular Second Premolar Migration: A Retrospective Study - İlhan Kaya; Ayşegül Türkmenoğlu; Halil Tolga Yüksel (Ankara University, 2021)
Purpose:To investigate the prevalence and radiographic characteristics of migrated mandibular second premolars byusing panoramic radiography.Materials amp; Methods:The previously taken 27758 panoramic radiographs were evaluated regarding the determining theprevalence of mandibular second premolar migration. Thirty-six radiographs were excluded from the study due to notproviding the inclusion criteria. 27722 radiographs were evaluated retrospectively by the same operator. In the diagnosisof migrated teeth, radiographic features and demographic characteristics were recorded.Results:Nine migrated second premolar teeth were detected in the evaluation of all the radiographs (%0.03). The meanage of the cases was 37 years. All the migrated teeth were impacted, unilateral and the average distance between normaland migrated location was 41 mm. In most of migration case (in 6 case) absence of first permanent molar tooth wasobserved.Conclusion:It is concluded that, if the mandibular second premolar tooth are not located at physiologic position on thedental arch, a panoramic radiographic examination should be recommended to view all the jaws and related structures.Early detection of dental migration may be beneficial to prevent the possible further complications.